PAN-Immune inflammation value: a new biomarker for diagnosing appendicitis in children?? - Nurcan Çoşkun; Mehmet Metin; Gül Doğan; Hülya İpek; Emre Demir; Çağatay Evrim Afşarlar (BMC Pediatrics)
Abstract Background This study investigates the potential of the pan-immune-inflammation values (PIV) index as a biomarker for diagnosing acute appendicitis in children and compares its performance with other systemic inflammatory markers. Methods A retrospective analysis of 1,514 pediatric patients aged 0–18 years with abdominal pain admitted between 2019 and 2023 was conducted. Patients were categorized into complicated, non-complicated appendicitis, negative appendectomy, and non-surgical treatment groups. Demographic and laboratory data were recorded, and PIV, Systemic Inflammation Index (SII), Systemic Inflammation Response Index (SIRI), Neutrophil-to-Lymphocyte Ratio (NLR), and Platelet-to-Lymphocyte Ratio (PLR) indices were calculated. Receiver Operating Characteristic (ROC) analysis was used to assess predictive performance, with optimal cut-offs evaluated for sensitivity, specificity, and multiple logistic regression (MLR) analyses. Results Based on Area Under the Curve (AUC), C-reactive Protein (CRP), lymphocyte, and PLR showed weak predictive value, while White Blood Cell Count (WBC), neutrophil, monocyte, NLR, SII, SIRI, and PIV demonstrated poor predictive value for appendicitis. Optimal cut-offs were 3.40 for NLR, 134.5 for PLR, 1010.3 for SII, 3.47 for SIRI, and 919.3 for PIV, with sensitivity and specificity values of 78.7%, 47.1% for NLR; 64.7%, 47.5% for PLR; 75.6%, 52% for SII; 71.5%, 57.3% for SIRI; and 72.2%, 54.1% for PIV. In the MLR model, PIV above 919.3 increased appendicitis likelihood 2.67-fold (95% Confidence Interval: 2.16–3.37). Conclusion Although PIV demonstrated potential as a novel biomarker for pediatric appendicitis, its diagnostic utility remains limited without supplementary clinical and radiological data. Larger prospective studies are recommended to validate these findings and improve clinical decision-making. PIV may serve as a supplementary tool in diagnosing pediatric appendicitis when used alongside other markers and diagnostic methods. Trial registration ‘retrospectively registered’.